Energy and fat intake in obese and lean children at varying risk of obesity. - McGloin, A; Livingstone, M; Greene, L; Webb, SE; Gibson, J; Jebb, SA; Cole, T; Coward, W; Wright, A; Prentice, A (2002)
OBJECTIVE: This study compared lean children at high risk (HR) and low risk (LR) of obesity and obese children (OB) to assess the relationship between their energy (EI) and fat intake and adiposity. DESIGN: Cross-sectional study of energy and fat intake in children, using 7-day weighed intakes validated by doubly labelled water (DLW) energy expenditure. SUBJECTS: A total of 114 pre-pubertal children, 50 HR (mean+/-s.d., 6.7+/-0.6 y, 25.7+/-4.8 kg, 21.3+/-6.6% body fat), 50 LR (mean+/-s.d., 6.6+/-0.8 y, 23.6+/-3.7 kg, 18.9+/-5.7% body fat) and 14 OB (mean+/-s.d., 6.8+/-1.0 y, 37.7+/-5.3 kg, 34.8+/-5.6% body fat). MEASUREMENTS: Body fatness was measured using deuterium dilution, total energy expenditure (TEE) by DLW and dietary intake using 7-day weighed records. RESULTS: EI was 98% of TEE in LR children, 95% in HR children and 86% in OB children. Although EI was similar in each group (LR, 7.03+/-1.26 MJ/day; HR, 7.30+/-1.46 MJ/day; OB, 7.55+/-1.67 MJ/day), obese +/-4.6%; P<0.05). There was a significant linear trend towards increasing fat intake (percentage energy) with increasing risk of obesity (P<0.05). While HR children were heavier and fatter than LR children (P<0.05), their EI and fat intake were not significantly greater (HR, 73+/-17 g, 37.3+/-4.4%). Dietary fat intake (percentage energy) was weakly but significantly related to body fatness (r(2)=0.05, P=0.02) by step-wise regression. Since energy from fat was the only macronutrient that was a significant predictor of body fatness, results were therefore analysed using quartiles of fat intake (percentage energy) as cut-offs. When grouped in this way children with the lowest intakes were leaner than those with the highest intakes (19.5+/-7.5 vs 24.9+/-9.4% body fatness; P<0.05). There was a significant trend for increasing fatness as fat intake increased (P<0.05). CONCLUSION: Fat intake is related to body fatness in childhood.